A THEORETICAL NOTE ON KERALA-STYLE DECENTRALIZED PLANNING - Prabhat Patnaik
The "Peoples' Plan campaign" in Kerala, which led to the devolution of nearly a third of the Plan outlay of the State to Local Self Government Institutions to spend on projects of their choice, has of late generated much controversy. Many have even argued that "decentralization" is a part of the imperialist agenda and that the Left's adoption of it represents a capitulation (which can be explained only through the "erroneous" activities and understanding of some leading Comrades). This entire line of criticism however misses a basic point, namely that the "decentralization" proposed by the Left, propagated through the Peoples' Plan campaign, and implemented during the years of LDF rule is fundamentally different from the "decentralization" promoted by the World Bank and other imperialist agencies. While the "decentralization" agenda of the Left is a means of carrying class-struggle forward, of buttressing the class-strength of the rural poor by developing institutions where they can, in principle, assert themselves directly and hence more effectively, the "decentralization" promoted by the imperialist agencies has precisely the opposite objective, of blunting class-struggle, of encouraging a scenario of "obedient-and-supplicant-villagers-being-patronized-by-NGOs", and of substituting the concept of the "Rights" of the people by the concept of "Self-Help". In pushing their agenda, it is in the interests of the imperialist agencies to pretend as if there is no difference between their programme and the Left programme. But for that very reason it is essential for the Left to emphasize in every possible manner the difference between the two agendas, to highlight the specificity of the imperialist agenda, if it is to defeat the latter